Factors Associated With Infant Bed-Sharing. (2nd February 2017) - Heere, Megan; Moughan, Beth; Alfonsi, Joseph; Rodriguez, Jennifer; Aronoff, Stephen
Objective: Bed-sharing is associated with sudden infant death syndrome and accidental suffocation and strangulation in bed. The purpose of this study was to identify risk factors for newborn bed-sharing.Methods: Postpartum mothers from a university maternity service were contacted by phone to complete a survey. Demographic and environmental data were collected; newborn bed-sharing and sleep environment were self-reported.Results: A total of 1261 mothers completed surveys; bed-sharing was reported by 79 mothers (6.3%). Multivariate logistic regression identified referral to a nurse (odds ratio [OR] = 10; 95% confidence interval [CI] = 4.5-30) and sleep location "other" than a crib, bassinet, or Pack and Play (OR = 7.1; 95% CI = 1.9-25.9) as factors associated with an increased risk of bed-sharing; formula feeding (OR = 0.4; 95% CI = 0.20-0.77) and crib sleeping (OR = 0.49; 95% CI = 0.26-0.86) reduced this risk.Conclusion: Infants with no identifiable places to sleep, significant health issues, and who are breastfed are more likely to bed-share. Interventional studies should be directed at these factors.